2019
DOI: 10.1007/s40473-019-00177-2
|View full text |Cite
|
Sign up to set email alerts
|

Examining Neural Reactivity to Gambling Cues in the Age of Online Betting

Abstract: Purpose of Review The goal of this review is to provide new insights as to how and why functional magnetic resonance imaging (fMRI) research on gambling cue reactivity can contribute to significant progress toward the understanding of gambling disorder. After having offered a detailed description of experimental paradigms and a comprehensive summary of findings related to gambling cue reactivity, the present review suggests methodological avenues for future research. Recent Findings The fMRI literature on prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 110 publications
(186 reference statements)
0
22
0
Order By: Relevance
“…The gambling landscape has significantly evolved in recent years and gambling opportunities have unprecedentedly exploded with the advent of Internet and mobile gambling (Brevers et al, 2019;Sharman et al, 2019). Moreover, involvement in gambling has tended to become normalized by advertisements, sponsorship, and popular movies (e.g., James Bond's Casino Royale; Campbell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The gambling landscape has significantly evolved in recent years and gambling opportunities have unprecedentedly exploded with the advent of Internet and mobile gambling (Brevers et al, 2019;Sharman et al, 2019). Moreover, involvement in gambling has tended to become normalized by advertisements, sponsorship, and popular movies (e.g., James Bond's Casino Royale; Campbell, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies probing cue reactivity in pathological gamblers have typically either used picture stimuli [4,5,30,[22][23][24][25][26][27][28][29] or real-life gambling environments (i.e. gambling facilities) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Initial strides towards this objective have been taken by neuroimaging research on cue–reactivity . Specifically, a recent functional magnetic resonance imaging study has shown that the brain processes information about sporting cues differently, depending on whether sports fans think about a sporting event with the intention of gambling on the outcome or think about it with the intention of merely watching it .…”
mentioning
confidence: 99%
“…From the standpoint of the present commentary, the examination of sports betting, cue–reactivity should greatly benefit from a multi‐level approach, featuring eye‐tracking measurements. Indeed, a key feature of a cue–reactivity paradigm is that it exposes participants to cues that depict real‐life (gambling) situations through visual and/or auditory stimulations . Hence, eye‐tracking procedures should offer innovative markers of cue–reactivity patterns that characterize the sports betting digitalized experience (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation